Saliency Ratio Based Torque Enhancement of Switched Reluctance Motor for EV Application - Ghani, Abdul (320981); Dr. Hassan Abdullah Khalid (Islamabad : USPCAS-E, NUST, 2023)
TH-508
Keywords: MS-EEP Thesis; MS Thesis